Politik Hukum Dan Transformasi Wahyu Ke Legislasi Di Indonesia - Andrizal, Andrizal; Johan, Marjohan; Bambang, Bambang Hermanto (Faculty of Law Universitas Lancang Kuning, 2024)
As a heterogeneous nation, the existence of Islamic law actually poses a threat to the integration of the unitary state of Indonesia. This has become an interesting phenomenon and has not failed to find common ground even in other Muslim countries. For this reason, this paper describes the process of transforming revelation into legal legislation and the role of legal politics in transforming revelation into legal legislation in Indonesia. The research method used is normative research. The transformation of revelation into legal legislation occurred after the death of the Prophet Muhammad, where his role and duties were transferred to the mujtahids. Islam as a legal system contains universal principles that can develop with the positive legal system adopted in Indonesia.